Magnetic chitosan microspheres: An efficient and recyclable adsorbent for the removal of iodide from simulated nuclear wastewater. (15th January 2022) - Li, Xin; Zeng, Danlin; He, Zhiyong; Ke, Ping; Tian, Yongsheng; Wang, Guanghui
Abstract: The efficient and recyclable magnetic chitosan microspheres (MCMs) were successfully synthesized to remove iodide from nuclear wastewater and characterized through XRD, FTIR, SEM, EDS, VSM, TGA and XPS. The characterization results indicated that the MCMs exhibited smooth spherical morphology and good magnetic properties. The removal potential of MCMs was investigated for iodide (I − ) anions at different conditions. From pH 3 to pH 9, MCMs performed the high I − removal efficiency (>90%). The maximum I − removal capacity of MCMs was up to 0.8087 mmol g −1 at 298 K, well-fitting with the pseudo-second-order and Sips models. Furthermore, the I − removal efficiency of MCMs still maintained more than 91% after five adsorption-desorption cycles, performing good regeneration and reusability. This study is expected to prompt the MCMs to become an efficient and recyclable biosorbent for iodide removal from nuclear wastewater. Graphical abstract: Unlabelled Image Highlights: The MCMs were successfully synthesized by the combined hydrothermal method and emulsion polymerization. The maximum I − anions removal capacity of MCMs was up to 0.8087 mmol g −1 at 298K. The MCMs exhibited high magnetic responsiveness and can be recycled using magnetic separation. The MCMs performed the I – removal efficiency of higher than 90% from pH 3 to 9. The MCMs can maintain the high I – removal efficiency (>91%) after five adsorption-desorption cycles.